Weaving Ontology. Patterns of Textile Structures from the Knot to the Digital Lace (diségno, 2021)
One of the fundamental technical design problems concerns the connection of the component parts of artefacts. In this sense, the ancient art of weaving presents interesting and topical aspects, which apply to the field of design and architecture and underline the truth of Gottfried Semper's statements regarding the classification of materials and construction techniques. The combination of digital technology and weaving patterns, derived from the development of the knot/button structure in weaving and then in lace, makes it possible to create textile structures that can be applied in many sectors and that have performance and aesthetic properties derived from the formal archetypes of fabric construction. Since the invention of the Jacquard loom in the 17th century, technological innovation has given a considerable boost to the textile sector. Starting from the sixteenth-century tradition of Milanese bobbin lace, passing through the twentieth-century interpretations of the schools linked to the Modern Movement and arriving at today's interpretations, the research aims to experiment the application of structures generated by digital algorithms for the production of artefacts and the valorisation of a heritage of knowledge. Having defined the basic elements, the weaving movements and the complete cycle to be repeated in the lace tradition, it is possible to recreate the formal structure through the geometric control of the shape and movement parameters.
Keywords: node; algorithm; linking; weaving; visual modeling